Adjuvant Use of Ivabradine in Acute Heart Failure due to Myocarditis. (27th September 2011) - Franke, Jennifer; Schmahl, Dorothee; Lehrke, Stephanie; Pribe, Regina; Bekeredjian, Raffi; Doesch, Andreas O.; Ehlermann, Philipp; Schnabel, Philipp; Katus, Hugo A.; Zugck, Christian
Abstract : We report two cases of young men in whom acute heart failure due to myocarditis was diagnosed. The patients had been transferred to the intensive care unit (ICU) with commencing symptoms of acute heart failure and consecutive multiorgan failure for further treatment and to evaluate the indication for implantation of a ventricular assist device or for high urgent orthotopic heart transplantation. In both patients, the I f -channel inhibitor ivabradine was administered off-label to provide selective heart rate reduction, and thus support hemodynamic stabilization. Though currently considered off-label use in patients suffering from severe hypotension and acute heart failure, the use of ivabradine may beneficially influence outcome by allowing optimization of the patient's heart rate concomitant to initial measures of clinical stabilization.